Lewensbeskoulike differensiasie in die onderwys* - Schutte, B. C. (Koers, 1981)
The fact that for many people the N in CNE (Christian National Education) often became more important than the C may be ascribed to a historical process. Opponents of the whole concept also did not understand that the Christian Afrikaner wanted a Christian education for his own children, and did not begrudge other people '‘other" education. The concept “National", however, has become a bogyman, and has come to be interpreted in terms o f the "National Party".